PENGUATAN TATA KELOLA KEUANGAN DAERAH BERDASARKAN HASIL INDEKS PENGELOLAAN KEUANGAN DAERAH - Siswantoro, Dodik; Hasna Nuzulia Yusmina, Khoirunnisa (Faculty of Economics and Business University of Mataram, 2023)
This study aims to evaluate the performance of regional financial governance in Klaten Regency based on Permendagri No 19 of 2020, which focuses on budget allocation in the APBD and budget absorption. This research is a case study with a qualitative approach. The research instruments were in-depth interviews, documentation studies, and direct observation at BPKPAD and Bappedalitbang Klaten Regency. The results of research on budget allocations in APBD show that there are human errors, a slow system, budget reallocations, differences in perceptions between regulators and regulates, and unclear and detailed rules. The absorption of the budget shows the role of planning, human resources, time management, and force majeure factors. The recommendation in this study is that the regulator can increase reviews related to the elaboration of the IPKD. It is advisable to organize training activities and technical guidance for measuring IPKD and implementing reward-punishment. For the Klaten Regency Government, it can improve coordination and socialization in the implementation of regional policies and consider human resources in terms of quality and quantity.